2021
DOI: 10.3389/fpsyt.2021.707293
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Organizational Support in Mental Health of Healthcare Workers During the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Background: Data support the link between the coronavirus disease 2019 (COVID-19) pandemic and mental distress in healthcare workers (HCWs). Although previous studies have documented the association between organizational policies and employees' psychological and mental status, there is still scant evidence regarding the effect of perceived organizational support (POS) on mental distress in HCWs during the pandemic.Aims: The present study aimed to assess the association between POS and mental distress in HCWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 33 publications
3
48
2
1
Order By: Relevance
“…Peer support appears to be necessary at this particular period, including support from colleagues and the hospital. A study in the Republic of Cyprus reported that organizational support was associated with HCWs' mental distress ( 28 ). In addition, another study in New York found that higher leadership support was linked to the lowest risk of depression, anxiety, and COVID-19-related post-traumatic symptoms ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peer support appears to be necessary at this particular period, including support from colleagues and the hospital. A study in the Republic of Cyprus reported that organizational support was associated with HCWs' mental distress ( 28 ). In addition, another study in New York found that higher leadership support was linked to the lowest risk of depression, anxiety, and COVID-19-related post-traumatic symptoms ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness can be seen as an interpersonal stressor that gives rise, for instance, to negative emotions and physiological reactivity, which is conducive to the nervous system’s unhealthy activity. In line with this, adults experiencing loneliness are also characterized by higher levels of anxiety, negative mood, and stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 95%
“…Chatzittofis et al found low POS to be associated with higher rates of depression, stress, and traumatic symptoms, indicating that the greater the POS, the better the employee MH. 27 This seems to have been particularly true during COVID-19. 27 Jin and Tang found higher POS experienced by employees at work to lower stress levels, further implying the correlation of POS to MH (POS→MH).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 96%
“… 18 Another definition was proposed by Chatzittofis et al, as it pertains to employees’ perceptions of the extent to which an organization expresses concern with maintaining employees’ physical, psychological, and mental wellbeing. 27 According to Malik and Neem, employees’ POS is a vital aspect of work culture for organizational environments that require employees to perform more than their job descriptions. 46…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation